Editorial [Hot Topic: Molecular and Clinical Aspects of Hereditary Hemorragic Telangiectasia: A Rare Disease Executive Editor: (Emilo Jirillo)] - Jirillo, Emilio (Current Pharmaceutical Design, 2006)
Hereditary Hemorragic Teleangiectasia or Osler-Weber-Rendu disease represents a rare genetic disorder which is under intensive investigation in view of its multidisciplinary aspects. In the present hot topic issue entitled: